Perencanaan dan Perancangan Pusat Pelatihan Wushu di Kota Denpasar, Bali - Muhamad Amin Yusuf; I Kadek Merta Wijaya; Gde Bagus Andhika Wicaksana (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
Denpasar has 4 sports Wushu colleges, from 4 wushu sports colleges in Denpasar which are used as training sites for Denpasar wushu athletes, there is no training center in the form of a training building, training activities still borrow places including Paradewa Bali Wushu which functions as a gym, Suryatama Wushu its function as futsal, Garuda Dewata Wushu functions as a Universal School, and Udayana Wushu UKM. Equipment is very minimal, especially the fields for taolu and sanda are also not available, even if they are bought, there is also no place to send them, they do not have standard dimensions of the Taolu and Sanda wushu fields, there is no grouping of taolu and sanda wushu fields, no facilities to support training activities. This does not have a match between the activities at the available facilities, even though the development of the number of athletes, the increase in fans, is supported by the potential achievements achieved each year. The purpose of designing a training center in the form of a training building with adequate infrastructure, capable of accommodating training activities for athletes, having standard field dimensions, as well as field grouping by applying the concept of completeness and comfort and applying modern architectural themes with new facilities, free columns, the layout of the room is in accordance with user activities, the shape of the building can respond to the direction of the wind, considering that sports activities will certainly make the atmosphere of the room stuffy and smelly.